Pemanfaatan Media Pembelajaran Berbasis Google Site untuk Meningkatkan Hasil Belajar Peserta didik pada Pembelajaran Bahasa Indonesia di Kelas V SDN 3 Mataram - Nurlaili, Nurlaili; Arjudin; Wardani, Fitria Kusuma (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to determine the utilization of Google Site–based learning media to improve students’ learning outcomes in Indonesian language learning. The research employed a Classroom Action Research (CAR) design, with the subjects being 30 fifth-grade students of SDN 3 Mataram. The instruments used included observation sheets and learning achievement tests. Based on the evaluation results in the pre-cycle stage, 26 students (86%) did not achieve mastery, while only 4 students met the passing criteria. In Cycle I, there was an improvement, with 21 students (70%) achieving mastery. In Cycle II, the results increased again, with 26 students (86%) reaching the mastery level. From these findings, it can be concluded that students’ learning outcomes improved significantly. Based on the learning achievement indicator, where at least 85% of students achieved a score of ≥70, it can be stated that the use of Google Site–based learning media effectively improved students’ learning outcomes in Indonesian language learning.